Palladium(0)-catalyzed arylative dearomatization of phenols. - Rousseaux, S; García-Fortanet, J; Del Aguila Sanchez, MA; Buchwald, S (2011)
The palladium-catalyzed arylative dearomatization of phenols to yield spirocyclohexadienone products in good to excellent yields has been developed. Preliminary results demonstrate that the formation of the spirocyclic all-carbon quaternary center can be accomplished with high levels of enantiocontrol (up to 91% ee).